1992
DOI: 10.1111/j.1558-5646.1992.tb00623.x
|View full text |Cite
|
Sign up to set email alerts
|

THE INFLUENCE OF DISPERSAL PATTERNS AND MATING SYSTEM ON GENETIC DIFFERENTIATION WITHIN AND BETWEEN POPULATIONS OF THE RED HOWLER MONKEY (ALOUATTA SENICULUS)

Abstract: Abstract. -The relationship between social structure and partitioning of genetic variance was examined in two red howler monkey populations (Wand G) in Venezuela, one of which (G) was undergoing rapid growth through colonization by new troops. Rates and patterns of gene flow had been determined through radiotelemetry and direct observation data on solitary migrants, and 10 years of troop censusing. Standard electrophoresis techniques were used to examine 29 loci in blood samples taken from 137 of the study ani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

6
124
2
4

Year Published

1997
1997
2010
2010

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 91 publications
(136 citation statements)
references
References 50 publications
6
124
2
4
Order By: Relevance
“…This observation contrasts markedly with the high levels of genetic variation shown by howler species from South America (A. seniculus, A. belzebul, and A. fusca;Lima et al 1990, Pope 1992, Sampaio et al 1996. It has been proposed that the low genetic diversity of Central American howlers is due to the action of random genetic drift (Froelich & Thorington 1982, Pope 1996, James et al 1997.…”
contrasting
confidence: 49%
See 4 more Smart Citations
“…This observation contrasts markedly with the high levels of genetic variation shown by howler species from South America (A. seniculus, A. belzebul, and A. fusca;Lima et al 1990, Pope 1992, Sampaio et al 1996. It has been proposed that the low genetic diversity of Central American howlers is due to the action of random genetic drift (Froelich & Thorington 1982, Pope 1996, James et al 1997.…”
contrasting
confidence: 49%
“…In addition, A. belzebul was polymorphic for EST, CA2, IDH, and LDH, and A. seniculus was polymorphic for EST, CA2, and MDH (Lima et al 1990, Sampaio et al 1996. Pope (1992) also found that A. seniculus from Venezuela was polymorphic for PGD, ADA, GPI, and two serum proteins (i.e., Tf and an unidentified protein). Contrary to our results, she found that A. seniculus from Venezuela was monomorphic for SOD.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations